Processing yield and chemical composition of rainbow trout (Oncorhynchus mykiss) with regard to body weight - Souza, Maria Luiza Rodrigues de; Macedo-viegas, Elisabete Maria [UNESP]; Zuanon, Jener Alexandre Sampaio; Carvalho, Maria Regina Barbieri de [UNESP]; Goes, Elenice Souza dos Reis (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
The influence of weight (W) category of the rainbow trout on processing yield and chemical composition of the entire eviscerated fish and fish fillet was analyzed. A completely randomized design was employed for processing variables (W1 = 300 to 370 g and W2 = 371 to 440) coupled to a 2 x 2 factorial scheme for the chemical composition (W1 and W2 and forms of presentation: fillet and whole eviscerated fish). W1 showed higher yield for entire eviscerated fish (83.00%) and head (13.27%), but a lower yield for the viscera (17.00%), when compared to W2. We did not affect abdominal muscle yield, fillet with or without skin, skin percentage and residues. There were significant differences between W for moisture (W1 = 72.30% and W2 = 71.15%) and lipids (CP1 = 7.96% and CP2 = 9.04%) rates. Fillet moisture contents (73.74%) and crude protein (19.05%) were higher (p < 0.01) than for entire eviscerated fish (69.71% and 17.81%, respectively). Ash (2.15%) and lipid (10.48%) rates were higher (p < 0.01) for entire fish when compared to those of fillets (1.16% and 6.52%, respectively). The slaughter of fish weighing between 300 and 370 g and their fillets are more adequate for the market.

O objetivo deste trabalho foi analisar a influência da categoria de peso (CP) da truta arco-íris sobre o rendimento do processamento e a composição centesimal do peixe inteiro eviscerado e do filé. O delineamento foi inteiramente casualizado para as variáveis do processamento (CP1 = 300 a 370 g e CP2 = 371 a 440 g) e em esquema fatorial 2 x 2 para composição centesimal (CP1 e CP2 e formas de apresentação (filé e peixe inteiro eviscerado). CP1 apresentou superior rendimento do peixe inteiro eviscerado (83,00%) e cabeça (13,27%), porém inferior para vísceras (17,00%), quando comparados à CP2. A CP não influenciou no rendimento dos músculos abdominais, filé com pele e sem pele, porcentagem de pele e resíduos. Houve diferenças significativas entre as CP para os teores de umidade (CP1 = 72,30% e CP2 = 71,15%) e lipídios (CP1 = 7,96% e CP2 = 9,04%). A umidade (73,74%) e a proteína bruta (19,05%) dos filés foram superiores (p < 0,01) do que para peixes inteiros eviscerados (69,71% e 17,81%, respectivamente). Teores de cinzas (2,15%) e lipídios (10,48%) foram superiores (p < 0,01) para peixes inteiros em relação aos filés (1,16% e 6,52%, respectivamente). Sugere-se o abate dos peixes com peso entre 300 a 370 g e a apresentação em filé como mais adequada para o consumo.
Rendimentos do processamento e composição química de truta arco-íris (Oncorhynchus mykiss) em relação ao peso corporal
Keywords: fillet yield; filleting; chemical composition; fish.; beneficiamento; filetagem; composição; centesimal; pescado